2016
DOI: 10.1038/srep21779
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plasma-activated compounds on melanogenesis and tyrosinase activity

Abstract: Many organic chemists around the world synthesize medicinal compounds or extract multiple compounds from plants in order to increase the activity and quality of medicines. In this work, we synthesized new eugenol derivatives (ED) and then treated them with an N2 feeding gas atmospheric pressure plasma jet (APPJ) to increase their utility. We studied the tyrosinase-inhibition activity (activity test) and structural changes (circular dichroism) of tyrosinase with ED and plasma activated eugenol derivatives (PAED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Similar findings were also noted with the compounds methyl cinnamate (structurally similar to curcumin) and methyl 3-phenylpropionate, where authors noted that the latter compound inhibited monophenolase activity with no effects on diphenolase activity but stimulated melanogenesis in cell cultures [40]. Another study also reported a similar observation in which the authors noted the inhibition of mushroom tyrosinase activity but the stimulation of melanogenesis in B16F10 cells by plasma-activated compounds [41]. This discrepancy can be explained by the differences between mushroom tyrosinase and human tyrosinase [42]; it has been reported that results from the mushroom tyrosinase assay may not be a true indicator of response from cellular melanin levels [43].…”
Section: Discussionsupporting
confidence: 72%
“…Similar findings were also noted with the compounds methyl cinnamate (structurally similar to curcumin) and methyl 3-phenylpropionate, where authors noted that the latter compound inhibited monophenolase activity with no effects on diphenolase activity but stimulated melanogenesis in cell cultures [40]. Another study also reported a similar observation in which the authors noted the inhibition of mushroom tyrosinase activity but the stimulation of melanogenesis in B16F10 cells by plasma-activated compounds [41]. This discrepancy can be explained by the differences between mushroom tyrosinase and human tyrosinase [42]; it has been reported that results from the mushroom tyrosinase assay may not be a true indicator of response from cellular melanin levels [43].…”
Section: Discussionsupporting
confidence: 72%
“…Rather low IC50 values have been determined also for resveratrol derivatives such as (E)-2,3-bis(4-hydroxyphenyl)acrylonitrile (IC50 = 5.06 μM) [169] and dihydrooxyresveratrol glucosides [170] (Figure 19). As to other natural phenol-inspired synthetic compounds [157][158][159][160][161], the best results have been reported for a carvacrol derivative containing a 3,5-dihydroxyphenyl moiety (IC 50 = 0.0167 µM) [159] ( Figure 19). Good inhibition properties have been exhibited also by some rhododendrol glycosides (IC 50 = 0.56-9.15 µM) [160] and eugenol derivatives (IC 50 ca.…”
Section: Synthetic Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 98%
“…Good inhibition properties have been exhibited also by some rhododendrol glycosides (IC50 = 0.56-9.15 μM) [160] and eugenol derivatives (IC50 ca. 8 μM) [161] (Figure 19).…”
Section: Synthetic Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
See 1 more Smart Citation
“…These aqueous reactions produce other relatively long‐lived RONS, such as hydrogen peroxide (H 2 O 2 ), nitrates (NO3), and nitrites (NO2) . RONS are involved in biological dysfunction, oxidative damage, cell destruction, and the activation of cell death pathways, and are believed to act as moderators or effectors in cell signaling cascades. We previously reported that N‐acetyl cysteine, an intracellular RONS scavenger, cancels the antitumor effect, that is, inhibits the anti‐proliferative effect of PAM .…”
Section: Introductionmentioning
confidence: 99%